Productivity Analysis Of Supply Chain Management Performance On Building Construction For Time Efficiency (Case Study Of RSHS Bandung Project) - Andriansyah, Andra; Saputra, Nendang; Anamy, Muhammad Zakaria; Rozy, Nikko (Politeknik Siber Cerdika Internasional, 2025)
This research can be a reference for other project management who want to implement supply chain management. Supply chain management is one of the important things in a construction project where the application of supply chain management will affect the success of a construction project both material management, type of work, and time schedule. Therefore, this study aims to reduce the risk of time losses and the effect of productivity performance on a project. By using a quantitative method that reviews the s-curve and distributes questionnaires, this study shows that the total deviation is 171.62 which results in an average deviation of 3.502 per week. Stating that the deviation results in a deviation of sure + and after conducting validity, reliability and satisfaction tests, the results show that supply chain management can accelerate and streamline time on building construction projects.